Suicidal behaviour and ideation in Guyana: A systematic literature review - Charlotte Shaw; Jaimee Stuart; Troy Thomas; Kairi Kõlves (Elsevier, 2022)
Summary: Background: The suicide rate in Guyana has consistently ranked as one of the highest in the world. This systematic review synthesises and critically analyses the existing literature on suicidal behaviours and ideation in Guyana. Methods: Systematic review with narrative synthesis was conducted following PRISMA guidelines. PubMed, PsychInfo, CINAHL and SCOPUS databases were searched until 31st March 2021. Articles which included the analysis of suicidal behaviour or suicidal ideation using data collected in Guyana were eligible for inclusion. Articles relating to the Jonestown mass murder-suicide event were excluded. This review was pre-registered with PROSPERO [CRD42021247669]. Findings: The search resulted in 318 articles, of which 24 met eligibility for inclusion. The majority were quantitative (n=18), relating to suicide mortality (n=9), and suicide attempt and suicidal ideation (n=9). Additionally, qualitative (n=5) and mixed-method (n=1) papers investigated the experiences of those bereaved by suicide, gatekeepers of suicidality, and adolescent students. Eleven studies were multinational, whilst 13 focused on Guyana. The quality of the publications varied. Interpretation: Despite high annual suicide rates in Guyana, published research is very limited. This review found preliminary evidence for key risk groups; males, female youth, and Indo-Guyanese ethnicity. Pesticide poisoning was identified as the most common method for suicide in Guyana. There is a need for local research investigating the context and narrative of suicide to inform culturally tailored prevention strategies. This study was limited to a narrative synthesis and may be impacted by publication bias. Funding: This research was supported by an Australian Government Research Training Program Scholarship through Griffith University Australia. Registration: Pre-registered in PROSPERO [CRD42021247669].